Ações do Serviço de Inspeção Federal em Frigorífico de Bovinos situado em Araguaína - Damalio, Vanessa Brito (Universidade Federal do Tocantins, 2023)
The curricular supervised work experience was done in December 1st, 2016 to February 10, 2017, In Federal Inspection Service (SIF) with number 723 at Meat factory - Boi Forte with a capacity of 700 cattle slaughter per day, located in Araguaína city of Tocantins state Brazil. The total hours of the working experience was 416 hours under Federal Auditor Dagoberto Machado Prata supervision the Veterinary Inspector Fredson Ronei Cândido and teacher’s orientation Doctor Cátia Maria de Oliveira Lobo. During this period, stages of pre-slaughtering, slaughtering and processing of meat were monitored, observing inspection actions service at all stages. Therefore, the internship allowed the insertion of the practice in the professional daily life, being an essential tool for good qualification of the graduate since it is the exclusive responsibility of the veterinarian, for example the inspection of products of animal origin.